INTEGRASI HUKUM ISLAM DAN HUKUM ADAT DALAM TRADISI BADAMAI MASYARAKAT BANJAR - Anisah Norlaila Hayati; Nor Fadillah (MAQASHIDUNA: Jurnal Hukum Keluarga Islam, 2026)
Abstract The Badamai tradition is an alternative dispute resolution system deeply rooted in the collective memory of the Banjar people since the era of the Sultan Adam Law (1835). As a local institution, this tradition plays a crucial role in maintaining social cohesion, but the dialectic of integrating norms within it requires in-depth theoretical study. This study aims to analyze the integration of Islamic law and customary law within the Badamai tradition as an instrument for informal conflict resolution in Banjar society. This research is a qualitative, descriptive field research. The approaches used are juridical-empirical (socio-legal) and legal pluralism. Primary data were obtained through in-depth interviews with Banjar traditional leaders (tetuha), peacemakers, and witnesses to the conflict. Secondary data were extracted from the Sultan Adam Law manuscript, Banjar cultural literature, and the concept of ishlah (reconciliation) in Islamic legal texts. The results show that the Badamai tradition effectively integrates the substantive values ​​of Islamic law (the principles of ishlah and benefit) with local Banjar culture. The family deliberation mechanism implemented was able to restore social harmony, maintain the dignity of the parties, and break the cycle of hostility without resorting to formal litigation. This study concludes that the integration of interlegality between Islamic and customary law in the Badamai tradition has successfully created a robust local restorative justice model. In the modern context, this tradition remains relevant and holds significant significance in supporting the harmonization of the national legal system based on local wisdom in Indonesia.